Log-normal nanograin-size distributions in nanostructured composites - Lu, Chungsheng; Lu, Y.; Shen, Y.; Mai, Y. (Taylor & Francis, 2008)
A key challenge in the fabrication of superhard nanocomposite films is how to control the distribution of grain sizes in these materials. High-resolution transmission electron microscopy has been used to measure nanograin-size distributions in the Ti-B-N films with various B contents. The results show that the mean grain size decreases with increase of B content and the grain-size distribution conforms to a log-normal function when the hardness approaches a maximum value. The transition from normal to log-normal distributions can be determined by analysis in terms of a minimum information criterion. The origin of a log-normal size distribution probably results from heterogeneity arising from a diffusion-drift process.